The treatment of acute myocardial infarction due to the occlusion of the left main coronary disease - (:unkn) unknown (My University, 2011)
Acute myocardial infarction (AMI) due to the occlusion of the left main coronary artery (LMCA) is a rare but serious condition in the era of percutaneus coronary intervention (PCI). Even more rare is AMI involved with both LMCA and its branches like trifurcartion or bifurcation: this is challenging for interventional cardiologists, because it involves the extension of the myocardium complicated by cardiogenic shock and its technical difficulties. Trifurcating coronary artery disease is a complex atherosclerotic process involving the origin of one or more of three side branches arising from a left main coronary vessel or trunk, with or without the involvement of LMCA itself. There is no classification or standardized methodology to treat LMCA disease in elective percutaneous intervention procedures. Furthermore, acute myocardial infarction presenting with left main coronary artery trifurcation lesion seems to be more troublesome, especially in young patients. Few series of PCI on significant lesions of the left main trifurcations have been described. Herein, we describe a patient who successfully underwent PCI and was supported by post intravascular ultrasound sonography and multislice computed angiography (MSCA), and after an uneventful follow-up with MSCA is now on the ninth month. © 2011 Via Medica.
Keywords: Left main coronary artery disease; Myocardial infarction; Trifurcation